This can be a great way to check your work or to see How to simplify expressions with fractions.

As we said, we simplify an exponential expression, x y, by multiplying x by itself y times. Therefore, to simplify ( a / b) c, we multiply a / b by itself c times. That's not so hard as long

Multiply fractions and simplify = 2 3 d) Given: x 2 (1 x + 3 2x) Use distributivity to write = x 2 (1 x + 3 2x) = x 2 × 1 x + x 2 × 3 2x Multiply the fractions in the above expression = x 2x + 3x 4x x is a

591+
Math Experts

7
Years in business

67535+
Delivered Orders